Reply - Bønnelykke,K; Vissing,NH; Sevelsted,A; Johnston,SL; Bisgaard,H (Journal of Allergy and Clinical Immunology, 2016)
Reply to: Minna Lukkarinen, Tuomas Jartti, The first rhinovirus-wheeze acts as a marker for later asthma in high-risk children, Journal of Allergy and Clinical Immunology